STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN EFEKTIVITAS KINERJA TENAGA ADMINISTRASI SEKOLAH - Sulis Anggraeni; Maulana Akbari; Besse Maryani; Agus Syukran; Aslamiah Aslamiah; Celia Cinantya (Universitas Islam Negeri Sumatera Utara Medan, 2025)
This study aims to identify the most effective leadership strategies in improving the performance of administrative staff at SMA Negeri 5 Banjarmasin and provide recommendations that can be implemented by the principal to optimize the administrative function. The techniques used in this study are direct interview techniques, observation, and documentation studies. The subjects of this study were the Principal of SMA Negeri 5 Banjarmasin and the Head of TAS SMA Negeri 5 Banjarmasin. The data obtained were analyzed using descriptive qualitative methods. The results of the study indicate that effective leadership strategies to improve the effectiveness of the performance of School Administrative Personnel (TAS) can be done by combining both approaches, namely the transformational and situational leadership approaches of leaders who can inspire and motivate staff but remain flexible in dealing with changing situations. Implementation of leadership strategies that combine transformational and situational approaches requires ongoing support, training, and evaluation. This is so that the administrative function continues to run well and according to objectives and is able to provide special attention to several administrative staff or other education personnel to be more skilled and trained, so that the administrative process can run more smoothly and effectively